KARAKTERISTIK DAN TINGKAT KOMPETENSI PENYULUH PERTANIAN SWADAYA DI KABUPATEN TANAH DATAR (Characteristic Profile And Competency Level Of Independent Agricultural Extension Workers In Tanah Datar Regency) - YUZINOSFRIS, YUZINOSFRIS; SYAHNI, RAHMAT; ASMAWI, ASMAWI (Universitas Mulawarman (University of Mulawarman), 2025)
This study aims to analyze the characteristics and competence levels of Independent Agricultural Extension Workers (IAEW) in Tanah Datar Regency. The research employed a descriptive quantitative method with a survey approach involving 85 respondents selected through a census technique. Data were collected using questionnaires and interviews, then analyzed using frequency and percentage tabulations. The findings show that most IAEWs are aged ≥50 years (62.81%), have a senior high school education (56.4%), and possess 4–6 years of extension experience (35.9%). Psychologically, the majority demonstrate high motivation (52.6%), broad cosmopolitan orientation (46.1%), and strong creativity and innovation (50%). Overall, the IAEW competence level falls into the moderate category (61.53%), followed by low (21.80%) and high (16.67%). The technical dimension shows the highest competence, while managerial, institutional, coordination, and collaboration aspects need further strengthening. These results highlight the importance of continuous managerial and institutional capacity-building programs to enhance the role of IAEWs as strategic partners of government extension workers in promoting sustainable agricultural development.